2014
DOI: 10.1021/ac503616d
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost and Highly Sensitive Immunosensing Platform for Aflatoxins Using One-Step Competitive Displacement Reaction Mode and Portable Glucometer-Based Detection

Abstract: Aflatoxins are highly toxic secondary metabolites produced by a number of different fungi and present in a wide range of food and feed commodities. Herein, we designed a simple and low-cost immunosensing platform for highly sensitive detection of mycotoxins (aflatoxin B1, AFB1, used as a model) on polyethylenimine (PEI)-coated mesoporous silica nanocontainers (PEI-MSN). The assay was carried out by using a portable personal glucometer (PGM) as the readout based on a competitive displacement reaction mode betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 48 publications
0
58
0
14
Order By: Relevance
“…Instead of using enzymes to generate glucose, an alternative strategy to provide the necessary link between target recognition and glucose levels is to directly release encapsulated glucose from nanocontainers, such as mesoporous silica (Fu et al, 2013, Gao et al, 2014, Hou et al, 2014, Tang et al, 2014, Wang et al, 2014b) and liposome (Zhao et al, 2015b), in response to a target recognition event. Gao and co-workers (Gao et al, 2014) reported the use of magnetic mesoporous particles as glucose nanocontainers, gated by antibody-mediated target responsive poly(ethyleneimine)-coated polystyrene microsphere (PEI-PSMS).…”
Section: Design Of the Bgm-based Biosensors For Ivds Of Non-glucosmentioning
confidence: 99%
“…Instead of using enzymes to generate glucose, an alternative strategy to provide the necessary link between target recognition and glucose levels is to directly release encapsulated glucose from nanocontainers, such as mesoporous silica (Fu et al, 2013, Gao et al, 2014, Hou et al, 2014, Tang et al, 2014, Wang et al, 2014b) and liposome (Zhao et al, 2015b), in response to a target recognition event. Gao and co-workers (Gao et al, 2014) reported the use of magnetic mesoporous particles as glucose nanocontainers, gated by antibody-mediated target responsive poly(ethyleneimine)-coated polystyrene microsphere (PEI-PSMS).…”
Section: Design Of the Bgm-based Biosensors For Ivds Of Non-glucosmentioning
confidence: 99%
“…AFB 1 -spiked peanut standards with various concentrations were prepared via our previously reported method. 52 Briefly, 5.0 g of the blank peanut sample milled by using a Midea food mixer (BP252AG, Guangdong, China) was initially extracted with 37.5 mL of MeOH/water (80:20, v/v) after being stirred for 60 min at room temperature (RT) followed by filtration. Then the extract (20 mL) was diluted into 60 mL of ultrapure water to acquire a final concentration of 20% (v/v) MeOH.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, electrochemical method has not been established to determine α-glucosidase activity and screen its inhibitor. On the other hand, one-step competitive displacement reaction strategy attracted substantial research interests recently in the analytical fields, because of its simplicity, specificity and reliable quantitative results (Ma et al, 2013;Salamon et al, 2015), although most of the present displacement reaction systems are applied to the detection of nucleic acids and the antigen-antibody reaction (Sapsford et al, 2002;Tang et al, 2014). It happens that the strategy was reported to be devoted to the investigation of the interaction between sugar and boronic acid , thus reversible covalent bonds between phenylboronic acid and 1,2-/1,3-cis-diols in aqueous solution have been used for the construction of molecular receptors (Yum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%